PENANDA JAMAK (Studi Perbandingan Antara Bahasa Arab dan Bahasa Indonesia) - Humaini, Arif (STUDI ARAB, 2016)
Indonesian and Arabic language are different, these two languages each have different systems at the level of phonemes, morphemes, phrases, clauses, and sentences.  Arabic belongs to flexion language, while the Indonesian language is not. Flexion language is defined as a process or a result of adding affixes to the base or root word for limiting the grammatical meaning. Therefore, the presence of the marker in Arabic is very important, while Indonesian language concerned with word order. The marker  is a tool that serves as affixes to express grammatical features or functions of the word, it was called in Arabic al-'alamat. There are many kinds of markers in Arabic, as there is a gender marker (mu'annats and Mudzakkar), a marker mufrod, plural marker, and so on. In this paper, we only specialize in plural marker. Plural marker in Indonesian mostly expressed in the form of reduplication,  reduplication consisting of nouns, verbs reduplication, and  reduplication adjectives. Also with the use of the word number, adding words para and kaum and by using penyukat which may indicate the plural of a word. Then in the Arabic language, the process of forming the plural marker is characterized by three things: first replace the letters or harakat, and both eliminate one of the letters, and the third gives additional or augmentation, either in the front, in the middle, or at the end of the word